Contribution of FBLN5 to Unstable Plaques in Carotid Atherosclerosis via mir128 and mir532–3p Based on Bioinformatics Prediction and Validation - Zheng, Lin; Yue, Xinyang; Li, Minhui; Hu, Jie; Zhang, Bojin; Zhang, Ruijing; Zheng, Guoping; Chen, Ruihan; Dong, Honglin (Frontiers in Genetics, 2022)
FBLN5 is a member of the short fibulins in the fibulin family of extracellular matrix/ matricellular proteins, which is involved in protein-protein interaction with the components of basement membrane and extracellular matrix proteins. It plays a key role in endothelial tissue in many vascular diseases. This study explored the relationship between FBLN5 and carotid atherosclerotic plaque stability and the regulatory mechanism of miRNA. Through difference gene and WGCNA analysis of GSE163154, it was found that FBLN5 was not only related to plaque stability, but also expressed the most significantly among different genes. At the same time, LASSO analysis was performed on genes obtained from the intersection of differential genes and strongly correlated blue and turquoise modules of WGCNA. The prediction models of 8 genes including FBLN5 were constructed by LASSO analysis and put into ROC for detection with an accuracy of 0.951. The low expression of FBLN5 in plaque tissue was confirmed by immunohistochemistry and Western Blot. GO and KEGG enrichment analyses showed that FBLN5 acted mainly through the maintenance of the cellular matrix and reactive oxygen species metabolic. At the same time, in order to further analyze the miRNA regulatory pathway of FBLN5, the upstream miRNAs of 8 predictive genes including FBLN5 were searched and the network diagram was constructed. It was found that hsa-mir-128 and hsa-mir-532-3p were the upstream regulatory factors of FBLN5, which were verified by PCR in human plaque tissues. The expression of both miRNAs was significantly up-regulated. Therefore, FBLN5 may play an important role in carotid atherosclerosis and is regulated by hsa-mir-128 and hsa-mir-532-3p.